PEMBELAJARAN BAHASA ARAB DI ERA POSMETODE - Muhbib Abdul Wahab (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2015)
This article is aimed to answer two essential problems; (1) development map of Arabic learning method from 1990s until today which has been formulated unclearly, and (2) developing Arabic learning in posmethod era by optimilizing teacher’s strategic role in the process of Arabic learning. This article used bibliographic sources from some books and articles in scientific journal about linguistic and Arabic learning. The interpretation data of academician thought and Arabic linguistic experts was done by using historical-critical approach and content analysis for substancial interpretation. B. Kumaravadivelu concept in Beyond Methods: Macrostrategies for Language Teaching (2003) which requires teacher to play three essential roles; pasif technician, reflective practician, and transformative intelectual is very inportant in Arabic learning in posmethod era. The principle of at-tharîqatu ahammu min al-mâddah (method is more important than content) can be developed to be main principle “spirit, profesionality and strategic role of language educator is more important in teaching Arabic than the method itself”, since basically there is no most appropriate and ideal method for any goals and situation of Arabic learning.DOI: 10.15408/a.v2i1.1519